ANALISIS KESALAHAN SISWA SMP DALAM MENYELESAIKAN SOAL MATERI ARITMATIKA SOSIAL - Mutia Fauzia; Asep Ikin Sugandi (IKIP Siliwangi, 2021)
The purpose of this study was to analyze the errors of class VIII students of one of the State Junior High Schools in Cimahi City in solving problems on social arithmetic material. The method used in this research is descriptive qualitative. The object is student errors when solving problems on social arithmetic, while the sample is taken arbitrarily and specifically with the subject of class VIII D SMP Negeri 3 Cimahi in the 2021-2022 academic year as many as 20 people. The data collection technique implements a test instrument of 5 essay questions, which will then describe the types of student errors in each item in solving social arithmetic problems. Data analysis reduces data, expresses data and draws conclusions. The results of the study revealed that there were several forms of errors, namely based on stages (1) reading (reading); (2) understand (comprehension); (3) determine the strategy (transformation); (4) the process of completion (process skills); and (5) writing answers (encoding).